Helium experiments on Alcator C-Mod in support of ITER early operations. (13th March 2018) - Kessel, C.E.; Wolfe, S.M.; Reinke, M.L.; Hughes, J.W.; Lin, Y.; Wukitch, S.J.; Baek, S.G.; Bonoli, P.T.; Chilenski, M.; Diallo, A.
Abstract: Helium majority experiments on Alcator C-Mod were performed to compare with deuterium discharges, and inform ITER early operations. ELMy H-modes were produced with a special plasma shape at B T = 5.3 T, I P = 0.9 MA, at q 95 3.8. The He fraction ranged over, n He, L / n L = 0.2–0.4, with n D, L / n L = 0.15–0.26, compared to D plasmas with n D, L / n L = 0.85–0.97. The power to enter the H-mode in He was found to be greater than 2 times that for D discharges, in the low density region <1.4 × 10 20 /m 3 . However, it appears to follow the D threshold for higher densities. The stored energies in the He discharges were about 80% of those in D, and about 40% higher net power was required to sustain them compared to D. Global particle confinement times for tungsten of τ W ∗ / τ E 4 were obtained with ELMy H-modes in He, however accumulation occurred when the ELMs were irregular and infrequent. The electron temperatures and densities in the pedestal were similar between D and He discharges, and the Δ T e / T e and Δ n e / n e values were similar or larger in He than D. The higher net power required to access the H-mode, and sustain it in flattop, for He discharges in C-Mod, imply some limitations for He operation in ITER.